CERAI GUGAT AKIBAT PERKAWINAN PAKSA (STUDI KASUS PERKARA NOMOR. 1189/Pdt.G/2021/PA.Sbr DALAM PERSPEKTIF PSIKOLOGI KELUARGA) - ESA THAHARA; EGI SAFITRI; Masyhari (UI Cirebon (Universitas Islam Cirebon), 2021)
Abstrack Marriage is not just a union between a man and a woman, but also unites steps and common goals so that domestic life can run well with minimal conflict. Marriage must also be carried out on the basis of the willingness of both parties without any element of coercion from anywhere. The method used in this study is qualitative, the main source of information is the related case files that the author obtained when carrying out field experience practices at the Sumber Religion Court. The results of this study indicate that this divorce occurred because the Plaintiff, who initially already had a lover, was in the end forced to marry the Defendant who was 21 years older than the Defendant. Therefore, the marriage which initially went well, then gradually worsened because the Plaintiff's heart still could not accept the Defendant. Keywords: Divorce, Forced Marriage, Psychology